1994
DOI: 10.1111/j.1476-5381.1994.tb13052.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated renal response to moxonidine and rilmenidine in one kidney‐one clip hypertensive rats

Abstract: 1I, non-adrenoceptor, imidazoline receptor agonists, such as moxonidine, increase urine flow rate and sodium excretion following infusion into the renal artery. The functions of these agonists in genetic and acquired models of hypertension have not been determined. 2 We therefore studied the renal effects of two known non-adrenoceptor, imidazoline receptor agonists, rilmenidine and moxonidine, in 1K-IC hypertensive and 1K-sham normotensive rats. Rilmenidine (0, 3, 10, 30 nmol kg-' min-') or moxonidine (0, 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…However, the protective effect of moxonidine against proteinuria was lost during the high-sodium diet. Consistent with our finding, it has been shown previously that the renoprotective effect of moxonidine is also markedly attenuated in one kidney-one clip hypertensive rats, a model of salt-sensitive arterial hypertension (Li et al 1994).…”
Section: Discussionsupporting
confidence: 81%
“…However, the protective effect of moxonidine against proteinuria was lost during the high-sodium diet. Consistent with our finding, it has been shown previously that the renoprotective effect of moxonidine is also markedly attenuated in one kidney-one clip hypertensive rats, a model of salt-sensitive arterial hypertension (Li et al 1994).…”
Section: Discussionsupporting
confidence: 81%
“…It was found to be equally efficacious in elderly hypertensive patients [44] and those who also suffered from diabetes [45], renal impairment [46] or left ventricular hypertrophy [47]. In animal studies, rilmenidine has been shown to increase sodium excretion and urine flow rates [48]. It is comparable with atenolol [49] and hydrochlorothiazide [47] as a first line antihypertensive.…”
Section: Historymentioning
confidence: 61%
“…Chronic treatment with the prototypic antidepressant imipramine, down-regulates I 1 -receptors in rat brainstem, without affecting ␣ 2 -adrenoceptors (Zhu et al, 1997). Also, renal I 1 -receptors are up-regulated by subpressor doses of angiotensin II infusion (Ernsberger et al, 1991), and in kidneys of SHR (El-Ayoubi et al, 2002b), whereas ␣ 2 -adrenoceptors are either unchanged or decreased in 1K1C rat kidneys (Li et al, 1994).…”
Section: Cardiac Imidazoline I 1 Receptors In Shr 449mentioning
confidence: 99%